2017
DOI: 10.1007/s13353-017-0415-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TLR7, TLR9, JAK2, and STAT3 genes in peripheral blood mononuclear cells from patients with systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a rare, chronic, multisystem autoimmune disease clinically characterized by progressive fibrosis of the skin and internal organs. The basic mechanism appears to involve endothelial cell injury, overproduction of extracellular matrix proteins, and aberrant immune activation. So far, there have been a few attempts to find genetic biomarkers for monitoring disease activity or for correlation with certain symptoms. In order to reveal reliable biomarkers, we analyzed the expression of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In contrast to our study, Vreca et al . [52] showed significant up‐regulation of TLR‐7 expression and significantly lower expression levels of the TLR‐9 in PBMCs of SSc patients. Moreover, they also observed that increased TLR‐7 expression correlated with disease activity, advanced disease and digital ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, Vreca et al . [52] showed significant up‐regulation of TLR‐7 expression and significantly lower expression levels of the TLR‐9 in PBMCs of SSc patients. Moreover, they also observed that increased TLR‐7 expression correlated with disease activity, advanced disease and digital ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…TLR8 is also atypically expressed on pDCs from SSc patients, driving IFN induction (Kioon et al, 2018). TLR9 expression is increased on human SSc skin biopsies and drives TGF-b-dependent fibroblast activation (Fang et al, 2016), while TLR7 expression is upregulated in SSc peripheral blood mononuclear cells (PBMCs) and correlates with late-stage disease (Vre ca et al, 2018). In patients with dermatomyositis and polymyositis, upregulation of TLR3, TLR7, and TLR9 contributes to the induction of type I IFNs and autoimmune responses (Kim et al, 2010;Tournadre et al, 2010).…”
Section: Reviewmentioning
confidence: 99%
“…In-vitro treatment of normal cutaneous fibroblasts with the TLR-9 ligand unmethylated CpG induced a profibrotic profile, involving autocrine TGF-β production. A recent paper detected a significant up-regulation of TLR7 gene expression in PBMCs of a group of SSc patients compared to a non-SSc group using the reverse transcriptionquantitative polymerase chain reaction (RT-qPCR) technique [41]. It is worth mention that several genes linked to autoimmunity are located on the X chromosome.…”
Section: Review Series: Innate Immunity In Systemic Sclerosismentioning
confidence: 99%
“…It is worth mention that several genes linked to autoimmunity are located on the X chromosome. Remarkably, among these genes are TLR-8 and TLR-7 [41]. Many autoimmune disorders, SSc included, are markedly sex-biased and studies support a gene-dose effect of the X chromosome loci in systemic lupus erythematosus (SLE) predisposition and, perhaps, establishment [42].…”
Section: Review Series: Innate Immunity In Systemic Sclerosismentioning
confidence: 99%